Heritability of prostate cancer: a tale of rare variants and common single nucleotide polymorphisms - Wu, Xifeng; Gu, Jian (Annals of Translational Medicine; Vol 4, No 10 (May 25, 2016): Annals of Translational Medicine (Focus on “State of the Art in Diagnostics of the Acute Coronary Syndrome”), 2016)
Prostate cancer (PCa) is the most common non-skin cancer men in developed countries. Despite years of research, no strong modifiable risk factor for PCa has been found. The two most significant cancer risk factors, smoking and obesity, do not appear to be strong risk factors for PCa. A recent systematic review and meta-analysis summarized the current literature of tobacco use and PCa mortality and incidence (1). This meta-analysis included 51 cohort studies (50,349 incident cases and 4,082,606 cohort participants) and found a dichotomized association between smoking and PCa risk. Current smoking was associated with an increased risk of PCa [rate ratio (RR): 1.06; 95% confidence interval (CI), 0.98–1.15] in studies completed in 1995 or earlier [before the prostate-specific antigen (PSA) screening era], and a reduced risk of PCa (RR: 0.84, 95% CI, 0.79–0.89) in studies completed afterward (after the wide spread of PSA screening).